Socioeconomic status is associated with stress hormones - Cohen, Sheldon; Doyle, William J; Baum, Andrew (Psychosomatic medicine, 2006)
We assess whether socioeconomic status (SES) is associated with basal levels of cortisol and catecholamines and determine if any association between SES and these hormones can be explained (is mediated) by behavioral, social, and emotional differences across the SES gradient. One hundred ninety-three adult subjects, including men and women and whites and African-Americans, provided 24-hour urine catecholamine samples on each of 2 days and seven saliva cortisol samples on each of 3 days beginning 1 hour after wake-up and ending 14 to 16 hours later. Values for both hormones were averaged across days to obtain basal levels. Lower SES (income and education) was associated with higher levels of cortisol and epinephrine and marginally higher levels of norepinephrine. These associations were independent of race, age, gender, and body mass. Low SES was also associated with a greater likelihood of smoking, of not eating breakfast, and with less diverse social networks. Further analyses provided evidence consistent with the hypothesis that these behavioral and social variables mediate the link between SES and the three stress hormones. Lower SES was associated in a graded fashion with higher basal levels of cortisol and catecholamines. These associations occurred independent of race, and the data were consistent with mediation by health practices and social factors.